A high-performance polyether TPU film and preparation method thereof

By using raw materials and process flow with specific proportions in polyether TPU films, the problem of insufficient antibacterial and tear resistance in water supplies is solved, and the preparation of high-performance polyether TPU films is realized. It has good aging resistance, airtightness, antibacteriality and tear resistance, and is suitable for water supplies and water entertainment purposes.

CN117844232BActive Publication Date: 2025-01-07DONGGUAN TEPUYOU ENVIRONMENTAL PROTECTION NEW MATERIAL CO LTD

Patent Information

Application Number
CN202311697082.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-12
Publication Date
2025-01-07
Estimated Expiration
2043-12-12

AI Technical Summary

Technical Problem

Polyether TPU films have problems with insufficient antibacterial and tear resistance in water supplies and water sports supplies.

Method used

The preparation method of high-performance polyether type TPU film is adopted, including dimer acid polyester polyol, modified polyester polyol, polyisocyanate, nitrile rubber, modified glass fiber, chain extender, catalyst, hexa methacrylic acid Raw materials such as fluorobutyl ester, coupling agent, antioxidant and antibacterial agent form films with good aging resistance, airtightness, antibacteriality and tear resistance through specific ratios and process flows.

Benefits of technology

Improve the aging resistance, airtightness, antibacteriality, tear resistance and mechanical properties of the membrane, extend the service life, and use biorenewable resources to prepare modified polyester polyols, reducing raw material costs and environmentally friendly Requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004600741240000101
    Figure BDA0004600741240000101
  • Figure BDA0004600741240000111
    Figure BDA0004600741240000111
Patent Text Reader

Abstract

The present application relates to the technical field of composite materials, and in particular to a high-performance polyether TPU film and a preparation method thereof. A high-performance polyether TPU film comprises the following raw materials by mass: 30-40 parts of dimer acid polyester polyol, 1015 parts of modified polyester polyol, 4060 parts of polyisocyanate, 1-3 parts of nitrile rubber, 10-15 parts of modified glass fiber, 58 parts of chain extender, 13 parts of catalyst, 58 parts of hexafluorobutyl methacrylate, 1-3 parts of coupling agent, 12 parts of antioxidant, and 0.1-0.5 parts of antibacterial agent. The polyether TPU film of the present application has good aging resistance, air permeability, antibacterial property, water resistance, waterproofness, tear resistance, and excellent mechanical properties, making it suitable for wide application in water supplies, water entertainment and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a high-performance polyether TPU film and a preparation method thereof. Background Art

[0002] Films made of thermoplastic polyurethane (TPU) are not only wear-resistant, flexible and highly elastic, but also have excellent moisture permeability and waterproof properties. They are also moderately priced, so they occupy the largest market share. However, in actual production, it is found that polyether TPU films used in water lifesaving products and water sports products still have the problem of poor comprehensive performance, especially antibacterial performance and tear resistance. Therefore, it is urgent to provide a solution to improve this problem. Summary of the invention

[0003] The purpose of this application is to provide a high-performance polyether TPU film and a preparation method thereof in response to the deficiencies of current technology. The polyether TPU film prepared in this application has good aging resistance, air tightness, antibacterial properties, water resistance, impact resistance, and tear resistance, and has high strength, good reliability, and a long service life.

[0004] In the first aspect, the present application provides a high-performance polyether TPU film, which adopts the following technical solution:

[0005] A high-performance polyether TPU film comprises the following raw materials in parts by weight: 30-40 parts of dimer acid polyester polyol, 10-15 parts of modified polyester polyol, 40-60 parts of polyisocyanate, 1-3 parts of nitrile rubber, 10-15 parts of modified glass fiber, 5-8 parts of chain extender, 1-3 parts of catalyst, 5-8 parts of hexafluorobutyl methacrylate, 1-3 parts of coupling agent, 1-2 parts of antioxidant and 0.1-0.5 parts of antibacterial agent.

[0006] By adopting the above technical scheme, in this high-performance polyether TPU film, various raw materials play different roles and synergistic effects, as follows: Dimer acid polyester polyol and modified polyester polyol: They are the main components of polyether TPU film, providing elasticity and plasticity. Dimer acid polyester polyol can be used to adjust the hardness and rigidity of the film, while modified polyester polyol introduces a large number of hydrophilic groups through hyperbranching technology, which improves the hydrophilicity and stability of the film. Polyisocyanate: As a cross-linking agent for the polymerization reaction, dimer acid polyester polyol and modified polyester polyol are polymerized with other components to form a high molecular weight polyester TPU film. Nitrile rubber: It has good oil resistance and weather resistance, and can improve the aging resistance and mechanical properties of the film. Modified glass fiber: It has good compatibility with other components and can improve the tear resistance of the polyether TPU film. Chain extender and catalyst: Chain extender is used to adjust the molecular weight and viscosity of the TPU film, and the catalyst promotes the polymerization reaction. Hexafluorobutyl methacrylate and coupling agent: Hexafluorobutyl methacrylate provides the film with water resistance and water resistance, and the coupling agent is used to enhance the adhesion between the modified glass fiber and other components. Antioxidant: Used to improve the aging resistance of the polyether TPU film. Antibacterial agent: The antibacterial agent prepared in this application has high-efficiency antibacterial properties, and can achieve an inhibition rate of more than 99.99% against Escherichia coli and Staphylococcus aureus, thereby improving the antibacterial properties and service life of the film. The above components play different roles in the polyether TPU film, and their synergistic effect makes the film have good aging resistance, air permeability, antibacterial properties, water resistance, water resistance and tear resistance.

[0007] Preferably, the molecular weight of the dimer acid polyester polyol is 2000, which is T-568 from Evonik Chemicals of Germany, and the acrylonitrile content in the nitrile rubber is 25-30%.

[0008] Preferably, the preparation method of the modified polyester polyol is as follows: 10-20 parts of citric acid and 15-25 parts of propylene glycol are placed in a reactor according to their weight fractions, heated to 130°C, introduced with nitrogen, and stirred for 1-2h; then 30-50 parts of gallic acid are added, stirred at 140°C for 1-2h, 0.2-1 parts of p-toluenesulfonic acid are added, and stirring is continued for 1-2h, during which the reaction system is vacuumed for 5min every 0.5h to remove small molecule by-products, and the reaction is stopped after there is no obvious change in the weight of the reaction system to obtain the modified polyester polyol.

[0009] By adopting the above technical scheme, in the preparation method of the modified polyester polyol, the citric acid and gallic acid used are two biorenewable resources, and a large number of hydrophilic groups are introduced by hyperbranching technology to prepare the modified polyester polyol. The modified polyester polyol has the following effects and synergistic effects in the preparation of high-performance polyether TPU film: hydrophilicity and stability: the modified polyester polyol has a large number of hydrophilic groups at the end, which can improve the hydrophilicity and stability of the polyether TPU film, so that it has good air permeability and water washability. Environmentally friendly: the modified polyester polyol prepared by biorenewable resources such as citric acid and gallic acid has environmentally friendly characteristics and meets the requirements of sustainable development. High degree of branching: hyperbranching technology makes the modified polyester polyol have a high degree of branching, which can increase the elasticity and plasticity of the polyether TPU film. Compatibility with other components: the modified polyester polyol has good compatibility with other components, especially with the modified glass fiber described in this application, which can improve the tear resistance of the polyether TPU film. In summary, modified polyester polyols have multiple effects in the preparation of high-performance polyether TPU films, such as hydrophilicity and stability, environmental friendliness, high degree of branching, and compatibility with other components. The synergistic effect makes the film have better performance.

[0010] Preferably, the polyisocyanate is at least one of liquefied diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 1,6-hexamethylene diisocyanate and isophorone diisocyanate.

[0011] Preferably, the modified glass fiber is obtained by mixing glass fiber and γ-methacryloxypropyltrimethoxysilane; wherein the mass ratio of the glass fiber to γ-methacryloxypropyltrimethoxysilane is 90:(2-5), and the diameter of the glass fiber is 8-20 μm.

[0012] By adopting the above technical scheme, in the preparation method of the modified glass fiber, the glass fiber and γ-methacryloxypropyltrimethoxysilane are mixed to obtain the modified glass fiber. Wherein, the mass ratio of the glass fiber and γ-methacryloxypropyltrimethoxysilane is 90:(2-5), and the diameter of the glass fiber is 8-20μm. The modified glass fiber has the following effects and synergistic effects in the preparation of high-performance polyether TPU film: Improved tear resistance: The modified glass fiber has good compatibility with other components, can increase the tear resistance of the polyether TPU film, and improve its strength and durability. Strengthening toughening effect: Due to the addition of modified glass fiber, a dispersed fiber network structure can be formed in the film, so that the toughness and impact resistance of the film are enhanced. Providing a reinforcing effect: Due to the addition of modified glass fiber, the rigidity and hardness of the film can be increased, providing better structural strength, so that the film has stronger durability and deformation resistance. Compatibility with other components: The modified glass fiber has good compatibility with other components and can form a good interaction with the matrix of the polyether TPU film to improve the overall performance of the film.

[0013] Preferably, the chain extender is at least one of ethylene glycol, propylene glycol, 1,3-butanediol and 2-methyl-1,3-propanediol.

[0014] Preferably, the catalyst is at least one of stannous isooctanoate, potassium 2-ethylhexanoate and dibutyltin dilaurate, and the antioxidant is one of antioxidant 1010, antioxidant 1076 and antioxidant 164, and antioxidant 1010, antioxidant 1076 and antioxidant 164 are produced by German company Bassef.

[0015] Preferably, the preparation method of the antibacterial agent is as follows: 0.78g of silver nitrate is added to 100mL of deionized water to prepare a 7.8g / L silver nitrate solution; 0.1g of sodium borohydride is added to 100mL of deionized water to prepare a 1g / L sodium borohydride solution; 20mL of the silver nitrate solution is added dropwise to 4% dilute ammonia water, while shaking until the precipitate is just dissolved, to obtain a silver ammonia solution; 20mL of the prepared silver ammonia solution is added to 80mL of aqueous polyurethane emulsion (solid content 32%) and stirred evenly to obtain a mixed solution, and 6mL of sodium borohydride solution is added to the mixed solution, stirred for reaction, to obtain the antibacterial agent.

[0016] By adopting the above technical scheme, in the preparation method of the antibacterial agent, a silver ammonia solution is obtained by reacting silver nitrate and sodium borohydride solution, and then the silver ammonia solution is mixed with an aqueous polyurethane emulsion and a sodium borohydride solution to finally obtain the antibacterial agent. The role of the antibacterial agent in the high-performance polyether TPU film is to improve the antibacterial performance: the antibacterial agent prepared in this application is added to the polyether TPU film, which can significantly improve the antibacterial rate of the film against Escherichia coli and Staphylococcus aureus, reaching more than 99.99%, and has excellent antibacterial properties.

[0017] Preferably, the coupling agent is a composition of 3-aminopropyltriethoxysilane, decyltrimethoxysilane, octyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:(2-4):(3-5):1.

[0018] By adopting the above technical scheme, in the present application, the coupling agent is a composition of 3-aminopropyl triethoxysilane, decyl trimethoxysilane, octyl trimethoxysilane and γ-glycidyl ether oxypropyl trimethoxysilane in a mass ratio of 3: (2-4): (3-5): 1. Its effects and synergistic effects are as follows: Improving the adhesion of the polyether TPU film: The coupling agent forms chemical bonds by chemically reacting with other components in the polyether TPU film, thereby enhancing the adhesion of the film and improving the stability of the film. Improving the wear resistance and heat resistance of the polyether TPU film: The introduction of the coupling agent can improve the wear resistance and heat resistance of the film and extend the service life of the film. Enhancing the interfacial compatibility of the polyether TPU film: The coupling agent can improve the compatibility of the modified glass fiber with other components and promote the interaction between them, thereby improving the tear resistance of the film. Synergistic effect: The coupling agent interacts with other components, and by jointly exerting their respective effects, they cooperate with each other to improve the overall performance of the polyether TPU film.

[0019] In a second aspect, the present application provides a method for preparing a high-performance polyether TPU film, using the following technical solution: A method for preparing a high-performance polyether TPU film, using the raw materials of the above-mentioned high-performance polyether TPU film, comprising the following steps:

[0020] S101, respectively add dimer acid polyester polyol, modified polyester polyol, polyisocyanate, nitrile rubber, modified glass fiber, chain extender, catalyst, hexafluorobutyl methacrylate, coupling agent, antioxidant and antibacterial agent into a stirring tank according to their mass fractions, set the speed to 300 rpm, control the temperature at 53° C., stir for 10-15 min, and obtain a mixture;

[0021] S102. The mixed material is transferred into a preheated twin-screw extruder for melt extrusion, and then granulated by a pelletizer, and finally blown into a film by a film blowing machine to obtain a high-performance polyether TPU film with a thickness of 0.01-0.03 mm; the extrusion temperatures of the twin-screw extruder from the feed port to the die are 140°C, 170°C, 180°C, 190°C, 200°C, 210°C, and 200°C respectively; the die head temperature of the film blowing machine is set to 180°C, 185°C, and 180°C.

[0022] In summary, the beneficial technical effects of this application are:

[0023] 1. Aging resistance: The film has good aging resistance, can maintain its performance for a long time, and is not easy to age and discolor.

[0024] 2. Breathability: The film has good breathability and can maintain air circulation to avoid stuffiness and airtightness.

[0025] 3. Antibacterial property: After adding antibacterial agent, the membrane has an antibacterial rate of more than 99.99% against Escherichia coli and Staphylococcus aureus, and has a good antibacterial effect.

[0026] 4. Water washing resistance: The film has excellent water washing resistance and can withstand water washing without being easily damaged.

[0027] 5. Waterproof: The film has good waterproof performance and can effectively block water penetration.

[0028] 6. Tear resistance: After adding modified glass fiber, the tear resistance of the membrane is improved and more durable.

[0029] 7. Excellent mechanical properties: The membrane has excellent mechanical properties and has high strength and toughness.

[0030] 8. Low cost of raw materials: modified polyester polyols are prepared using bio-renewable resources such as citric acid and gallic acid. No organic solvents are used in the preparation process, the operation is simple, and the raw material cost is low.

[0031] 9. Environmental friendliness: The modified polyol prepared in this application is an environmentally friendly material with good hydrophilicity and stability. DETAILED DESCRIPTION

[0032] The embodiments of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If the specific conditions are not specified in the examples, the conditions recommended by the manufacturer are followed. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially. Antioxidant 1010, antioxidant 1076 and antioxidant 164 are produced by German Bassif Company.

[0033] Example 1

[0034] A high-performance polyether TPU film includes the following raw materials in mass fractions: 30 kg of dimer acid polyester polyol, 10 kg of modified polyester polyol, 40 kg of liquefied diphenylmethane diisocyanate, 1 kg of nitrile rubber, 10 kg of modified glass fiber, 5 kg of ethylene glycol, 1 kg of stannous isooctanoate, 5 kg of hexafluorobutyl methacrylate, 1 kg of coupling agent, 1 kg of antioxidant 1010, and 0.1 kg of antibacterial agent. The molecular weight of dimer acid polyester polyol is 2000, which is German Evonik Chemical T-568, the acrylonitrile content in the nitrile rubber is 25%, and the coupling agent is a composition of 3-aminopropyl triethoxysilane, decyl trimethoxysilane, octyl trimethoxysilane and γ-glycidyl ether oxypropyl trimethoxysilane in a mass ratio of 3:2:3:1.

[0035] The preparation method of the modified polyester polyol is as follows: according to the mass fraction, 10 kg of citric acid and 15 kg of propylene glycol are put into a reactor, heated to 130° C., nitrogen is introduced, and stirred for 1 hour; then 30 kg of gallic acid is added, stirred at 140° C. for 1 hour, 0.2-1 kg of p-toluenesulfonic acid is added, and stirring is continued for 1 hour. During this period, the reaction system is vacuumed for 5 minutes every 0.5 hour to remove small molecular by-products, and the reaction is stopped after there is no obvious change in the weight of the reaction system to obtain the modified polyester polyol.

[0036] The modified glass fiber is obtained by mixing glass fiber and γ-methacryloxypropyltrimethoxysilane; wherein the mass ratio of the glass fiber to γ-methacryloxypropyltrimethoxysilane is 90:2, and the diameter of the glass fiber is 8-20 μm.

[0037] The preparation method of the antibacterial agent is as follows: 0.78g of silver nitrate is added into 100mL of deionized water to prepare a 7.8g / L silver nitrate solution; 0.1g of sodium borohydride is added into 100mL of deionized water to prepare a 1g / L sodium borohydride solution; 20mL of the silver nitrate solution is dropwise added with 4% dilute ammonia water while dropping and shaking until the precipitate is just dissolved to obtain a silver ammonia solution; 20mL of the prepared silver ammonia solution is added into 80mL of an aqueous polyurethane emulsion with a solid content of 32% and stirred evenly to obtain a mixed solution, and 6mL of the sodium borohydride solution is added into the mixed solution, stirred for reaction, and the antibacterial agent is obtained.

[0038] A method for preparing a high-performance polyether TPU film, using the raw material of the high-performance polyether TPU film, comprises the following steps:

[0039] S101, respectively add dimer acid polyester polyol, modified polyester polyol, liquefied diphenylmethane diisocyanate, nitrile rubber, modified glass fiber, ethylene glycol, stannous isooctanoate, hexafluorobutyl methacrylate, coupling agent, antioxidant 1010 and antibacterial agent into a stirring tank according to their mass fractions, set the speed to 300 rpm, control the temperature at 53° C., stir for 10 min, and obtain a mixture;

[0040] S102. The mixed material is transferred into a preheated twin-screw extruder for melt extrusion, and then granulated by a pelletizer. Finally, it is blown into a film by a film blowing machine to obtain a high-performance polyether TPU film with a thickness of 0.01 mm; the extrusion temperatures of the twin-screw extruder from the feed port to the die are 140°C, 170°C, 180°C, 190°C, 200°C, 210°C, and 200°C respectively; the die head temperature of the film blowing machine is set to 180°C, 185°C, and 180°C.

[0041] Example 2

[0042] A high-performance polyether TPU film includes the following raw materials in mass fractions: 40kg of dimer acid polyester polyol, 15kg of modified polyester polyol, 60kg of 2,4'-diphenylmethane diisocyanate, 3kg of nitrile rubber, 15kg of modified glass fiber, 8kg of propylene glycol, 3kg of potassium 2-ethylhexanoate, 8kg of hexafluorobutyl methacrylate, 3kg of coupling agent, 10762kg of antioxidant, and 0.5kg of antibacterial agent. The molecular weight of dimer acid polyester polyol is 2000, which is German Evonik Chemical T-568, the acrylonitrile content in the nitrile rubber is 30%, and the coupling agent is a composition of 3-aminopropyl triethoxysilane, decyl trimethoxysilane, octyl trimethoxysilane and γ-glycidyl ether oxypropyl trimethoxysilane in a mass ratio of 3:4:5:1.

[0043] The preparation method of the modified polyester polyol is as follows: according to the mass fractions, 20 kg of citric acid and 25 kg of propylene glycol are put into a reactor, heated to 130° C., nitrogen is introduced, and stirred for 2 hours; then 50 kg of gallic acid is added, stirred at 140° C. for 2 hours, 1 kg of p-toluenesulfonic acid is added, and stirring is continued for 2 hours. During this period, the reaction system is vacuumed for 5 minutes every 0.5 hours to remove small molecular by-products, and the reaction is stopped after there is no obvious change in the weight of the reaction system to obtain the modified polyester polyol.

[0044] The modified glass fiber is obtained by mixing glass fiber and γ-methacryloxypropyltrimethoxysilane; wherein the mass ratio of the glass fiber to γ-methacryloxypropyltrimethoxysilane is 90:5, and the diameter of the glass fiber is 8-20 μm.

[0045] The preparation method of the antibacterial agent is as follows: 0.78g of silver nitrate is added into 100mL of deionized water to prepare a 7.8g / L silver nitrate solution; 0.1g of sodium borohydride is added into 100mL of deionized water to prepare a 1g / L sodium borohydride solution; 20mL of the silver nitrate solution is dropwise added with 4% dilute ammonia water, while being shaken while being dropped, until the precipitate is just dissolved, to obtain a silver ammonia solution; 20mL of the prepared silver ammonia solution is added into 80mL of an aqueous polyurethane emulsion with a solid content of 32%, and stirred evenly to obtain a mixed solution, and 6mL of the sodium borohydride solution is added into the mixed solution, and stirred for reaction, to obtain the antibacterial agent.

[0046] A method for preparing a high-performance polyether TPU film, using the raw material of the high-performance polyether TPU film, comprises the following steps:

[0047] S101, respectively add dimer acid polyester polyol, modified polyester polyol, 2,4'-diphenylmethane diisocyanate, nitrile rubber, modified glass fiber, propylene glycol, potassium 2-ethylhexanoate, hexafluorobutyl methacrylate, coupling agent, antioxidant 1076 and antibacterial agent into a stirring tank according to their mass fractions, set the speed to 300 rpm, control the temperature at 53° C., stir for 15 min, and obtain a mixture;

[0048] S102. The mixed material is transferred into a preheated twin-screw extruder for melt extrusion, and then granulated by a pelletizer. Finally, it is blown into a film by a film blowing machine to obtain a high-performance polyether TPU film with a thickness of 0.03 mm; the extrusion temperatures of the twin-screw extruder from the feed port to the die are 140°C, 170°C, 180°C, 190°C, 200°C, 210°C, and 200°C respectively; the die head temperature of the film blowing machine is set to 180°C, 185°C, and 180°C.

[0049] Example 3

[0050] A high-performance polyether TPU film comprises the following raw materials in parts by mass: 35 kg of dimer acid polyester polyol, 13 kg of modified polyester polyol, 50 kg of 1,6-hexamethylene diisocyanate, 2 kg of nitrile rubber, 13 kg of modified glass fiber, 6 kg of 1,3-butanediol, 2 kg of dibutyltin dilaurate, 6 kg of hexafluorobutyl methacrylate, 2 kg of coupling agent, 1.5 kg of antioxidant 164, and 0.3 kg of antibacterial agent. The molecular weight of the dimer acid polyester polyol is 2000, which is T-568 produced by Evonik Chemicals of Germany. The acrylonitrile content in the nitrile rubber is 28%. The coupling agent is a composition of 3-aminopropyl triethoxysilane, decyl trimethoxysilane, octyl trimethoxysilane and γ-glycidyloxypropyl trimethoxysilane in a mass ratio of 3:3:4:1.

[0051] The preparation method of the modified polyester polyol is as follows: according to the mass fractions, 15 kg of citric acid and 20 kg of propylene glycol are put into a reactor, heated to 130° C., nitrogen is introduced, and stirred for 1.5 hours; then 40 kg of gallic acid is added, stirred at 140° C. for 1.5 hours, 0.6 kg of p-toluenesulfonic acid is added, and stirring is continued for 1.5 hours. During this period, the reaction system is vacuumed for 5 minutes every 0.5 hours to remove small molecular by-products, and the reaction is stopped after there is no obvious change in the weight of the reaction system to obtain the modified polyester polyol.

[0052] The modified glass fiber is obtained by mixing glass fiber and γ-methacryloxypropyltrimethoxysilane; wherein the mass ratio of the glass fiber to γ-methacryloxypropyltrimethoxysilane is 90:4, and the diameter of the glass fiber is 8-20 μm.

[0053] The preparation method of the antibacterial agent is as follows: 0.78g of silver nitrate is added into 100mL of deionized water to prepare a 7.8g / L silver nitrate solution; 0.1g of sodium borohydride is added into 100mL of deionized water to prepare a 1g / L sodium borohydride solution; 20mL of the silver nitrate solution is dropwise added with 4% dilute ammonia water, while being shaken while being dropped, until the precipitate is just dissolved, to obtain a silver ammonia solution; 20mL of the prepared silver ammonia solution is added into 80mL of an aqueous polyurethane emulsion with a solid content of 32%, and stirred evenly to obtain a mixed solution, and 6mL of the sodium borohydride solution is added into the mixed solution, and stirred for reaction, to obtain the antibacterial agent.

[0054] A method for preparing a high-performance polyether TPU film, using the raw material of the high-performance polyether TPU film, comprises the following steps:

[0055] S101, respectively add dimer acid polyester polyol, modified polyester polyol, 1,6-hexamethylene diisocyanate, nitrile rubber, modified glass fiber, 1,3-butanediol, dibutyltin dilaurate, hexafluorobutyl methacrylate, coupling agent, antioxidant 164 and antibacterial agent into a stirring tank according to their mass fractions, set the speed to 300 rpm, control the temperature at 53° C., stir for 13 min, and obtain a mixture;

[0056] S102. The mixed material is transferred into a preheated twin-screw extruder for melt extrusion, and then granulated by a pelletizer. Finally, it is blown into a film by a film blowing machine to obtain a high-performance polyether TPU film with a thickness of 0.02 mm; the extrusion temperatures of the twin-screw extruder from the feed port to the die are 140°C, 170°C, 180°C, 190°C, 200°C, 210°C, and 200°C respectively; the die head temperature of the film blowing machine is set to 180°C, 185°C, and 180°C.

[0057] Example 4

[0058] A high-performance polyether TPU film includes the following raw materials in mass fractions: 35kg of dimer acid polyester polyol, 13kg of modified polyester polyol, 50kg of isophorone diisocyanate, 2kg of nitrile rubber, 13kg of modified glass fiber, 6kg of 2-methyl-1,3-propylene glycol, 2kg of stannous isooctanoate, 6kg of hexafluorobutyl methacrylate, 2kg of coupling agent, 1.5kg of antioxidant 1010, and 0.3kg of antibacterial agent. The molecular weight of dimer acid polyester polyol is 2000, which is German Evonik Chemical T-568, the acrylonitrile content in the nitrile rubber is 28%, and the coupling agent is a composition of 3-aminopropyl triethoxysilane, decyl trimethoxysilane, octyl trimethoxysilane and γ-glycidyl ether oxypropyl trimethoxysilane in a mass ratio of 3:3:4:1.

[0059] The preparation method of the modified polyester polyol is as follows: according to the mass fractions, 15 kg of citric acid and 20 kg of propylene glycol are put into a reactor, heated to 130° C., nitrogen is introduced, and stirred for 1.5 hours; then 40 kg of gallic acid is added, stirred at 140° C. for 1.5 hours, 0.6 kg of p-toluenesulfonic acid is added, and stirring is continued for 1.5 hours. During this period, the reaction system is vacuumed for 5 minutes every 0.5 hours to remove small molecular by-products, and the reaction is stopped after there is no obvious change in the weight of the reaction system to obtain the modified polyester polyol.

[0060] The modified glass fiber is obtained by mixing glass fiber and γ-methacryloxypropyltrimethoxysilane; wherein the mass ratio of the glass fiber to γ-methacryloxypropyltrimethoxysilane is 90:4, and the diameter of the glass fiber is 8-20 μm.

[0061] The preparation method of the antibacterial agent is as follows: 0.78g of silver nitrate is added into 100mL of deionized water to prepare a 7.8g / L silver nitrate solution; 0.1g of sodium borohydride is added into 100mL of deionized water to prepare a 1g / L sodium borohydride solution; 20mL of the silver nitrate solution is dropwise added with 4% dilute ammonia water, while being shaken while being dropped, until the precipitate is just dissolved, to obtain a silver ammonia solution; 20mL of the prepared silver ammonia solution is added into 80mL of an aqueous polyurethane emulsion with a solid content of 32%, and stirred evenly to obtain a mixed solution, and 6mL of the sodium borohydride solution is added into the mixed solution, and stirred for reaction, to obtain the antibacterial agent.

[0062] A method for preparing a high-performance polyether TPU film, using the raw material of the high-performance polyether TPU film, comprises the following steps:

[0063] S101, respectively add dimer acid polyester polyol, modified polyester polyol, isophorone diisocyanate, nitrile rubber, modified glass fiber, 2-methyl-1,3-propanediol, stannous isooctanoate, hexafluorobutyl methacrylate, coupling agent, antioxidant 1010 and antibacterial agent into a stirring tank according to their mass fractions, set the speed to 300 rpm, control the temperature at 53° C., stir for 13 min, and obtain a mixture;

[0064] S102. The mixed material is transferred into a preheated twin-screw extruder for melt extrusion, and then granulated by a pelletizer. Finally, it is blown into a film by a film blowing machine to obtain a high-performance polyether TPU film with a thickness of 0.02 mm; the extrusion temperatures of the twin-screw extruder from the feed port to the die are 140°C, 170°C, 180°C, 190°C, 200°C, 210°C, and 200°C respectively; the die head temperature of the film blowing machine is set to 180°C, 185°C, and 180°C.

[0065] Comparative Example 1

[0066] The same as Example 4, except that an equal amount of dimer acid polyester polyol is used instead of the modified polyester polyol prepared in the present application.

[0067] Comparative Example 2

[0068] The same as Example 4, except that an equal amount of glass fiber is used to replace the modified glass fiber prepared in the present application.

[0069] Comparative Example 3

[0070] The same as Example 4, except that an equal amount of 3-aminopropyltriethoxysilane is used instead of the coupling agent, which is a composition of 3-aminopropyltriethoxysilane, decyltrimethoxysilane, octyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:3:4:1.

[0071] Comparative Example 4

[0072] The same as Example 4, except that an equal amount of decyltrimethoxysilane is used instead of the coupling agent, which is a composition of 3-aminopropyltriethoxysilane, decyltrimethoxysilane, octyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:3:4:1.

[0073] Comparative Example 5

[0074] The same as Example 4, except that an equal amount of octyl trimethoxy silane is used instead of the coupling agent, which is a composition of 3-aminopropyl triethoxy silane, decyl trimethoxy silane, octyl trimethoxy silane and γ-glycidyloxypropyl trimethoxy silane in a mass ratio of 3:3:4:1.

[0075] Comparative Example 6

[0076] The same as Example 4, except that an equal amount of γ-glycidyloxypropyltrimethoxysilane is used instead of the coupling agent, which is a composition of 3-aminopropyltriethoxysilane, decyltrimethoxysilane, octyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:3:4:1.

[0077] Performance Testing

[0078] The high performance polyether TPU films prepared in Examples 1-4 and Comparative Examples 1-6 were tested for performance, and the results are shown in Table 1.

[0079] Water vapor permeability test: refer to GB / T 12704-1991 standard, use water vapor permeability tester to test the water vapor permeability of high-performance polyether TPU film. The experimental test parameters are set at 38°C, 2% relative humidity, and 0.5m / s airflow. Each sample is tested three times and the average value is taken.

[0080] Static contact angle test: Use an optical contact angle tester to test the hydrophobicity of the high-performance polyether TPU film, measure the contact angle of water droplets on the surface of the high-performance polyether TPU film, and take the average value of multiple measurements;

[0081] Water pressure resistance test: refer to GB / T4744-1997 standard, use water permeability tester to test the water pressure resistance of the prepared high-performance polyether TPU film, select the pressure increasing method, the pressure increasing speed is 6.0kPa / min, and the pressure is increased until three small water drops appear on different areas of the high-performance polyether TPU film. The pressure value at this time is the water pressure resistance value of the high-performance polyether TPU film. The sample size is 20cm×20cm. Each sample is tested three times and the average value is taken;

[0082] Tensile properties: Cut the sample into 3mm×2cm strips and use a strength tester to test its mechanical properties. The tensile rate is set at 50mm / min, and each sample is measured 15 times to take the average value;

[0083] Peel strength: The high-performance polyether TPU film was cut into strips with a width of 25 mm and a length of 200 mm, and hot-pressed and bonded on the polyester fabric using a sealing machine. The T-peel strength was measured at a speed of 100 mm / min using a tensile testing machine. The implementation standard was GB / T2791-1995.

[0084] Water resistance test: the dried high-performance polyether TPU film is immersed in 80°C deionized water for 7 days, and then the sample is taken out and dried to test the tensile strength. The method for testing the tensile strength is the same as the above-mentioned tensile test method;

[0085] Antibacterial performance: tested according to GB / T 20944.3-2008, the experimental bacteria are Gram-positive bacteria Staphylococcus aureus (ATCC 6538);

[0086] Washability: The high-performance polyether TPU film to be tested was washed 100 times in a drum washing machine, and then the antibacterial property was tested; Tear resistance: The test was conducted in accordance with the ISO34-1 test standard.

[0087] Table 1

[0088]

[0089]

[0090] As shown in Table 1, the high-performance polyether TPU films prepared in Examples 1-4 have a tensile strength of ≥46.3 MPa, a water pressure resistance of ≥13468 mmH2O, and a moisture permeability of ≥23675 g / m 2 d. Peel strength ≥4.46N / cm, water contact angle ≥177.6, antibacterial rate ≥99.9%, excellent washability, tear resistance, water resistance, and comprehensive performance, making it suitable for a wide range of applications in water supplies, water entertainment and other fields.

[0091] As can be seen from Table 1, the performance comparison analysis of the high-performance polyether TPU film prepared in Example 4 and Comparative Example 1 shows that the high-performance polyether TPU film prepared by the modified polyester polyol prepared in the present application has better performance.

[0092] As can be seen from Table 1, the performance comparison analysis of the high-performance polyether TPU film prepared in Example 4 and Comparative Example 2 shows that the high-performance polyether TPU film prepared by using the modified glass fiber prepared in the present application has better performance.

[0093] As can be seen from Table 1, the performance comparison analysis of the high-performance polyether TPU films prepared in Example 4 and Comparative Examples 3-6 shows that the coupling agent is a composition of 3-aminopropyltriethoxysilane, decyltrimethoxysilane, octyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:3:4:1, and the synergistic effect between them is utilized to further improve the comprehensive performance of the high-performance polyether TPU film.

[0094] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. A method for preparing a high-performance polyether TPU film, characterized in that: The invention comprises the following raw materials in parts by weight: 30-40 parts of dimer acid polyester polyol, 10-15 parts of modified polyester polyol, 40-60 parts of polyisocyanate, 1-3 parts of nitrile rubber, 10-15 parts of modified glass fiber, 5-8 parts of chain extender, 1-3 parts of catalyst, 5-8 parts of hexafluorobutyl methacrylate, 1-3 parts of coupling agent, 1-2 parts of antioxidant and 0.1-0.5 parts of antibacterial agent; the molecular weight of the dimer acid polyester polyol is 2000, which is T-568 of Evonik Chemical of Germany; the acrylonitrile content in the nitrile rubber is 25-30%; The preparation method of the modified polyester polyol is as follows: according to the mass fraction, 10-20 parts of citric acid and 15-25 parts of propylene glycol are put into a reactor, heated to 130° C., nitrogen is introduced, and stirred for 1-2 hours; then 30-50 parts of gallic acid are added, stirred at 140° C. for 1-2 hours, 0.2-1 parts of p-toluenesulfonic acid are added, and stirring is continued for 1-2 hours, during which the reaction system is vacuumed for 5 minutes every 0.5 hours to remove small molecular by-products, and the reaction is stopped after there is no obvious change in the weight of the reaction system to obtain the modified polyester polyol; The polyisocyanate is at least one of liquefied diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 1,6-hexamethylene diisocyanate and isophorone diisocyanate; The modified glass fiber is obtained by mixing glass fiber and γ-methacryloxypropyltrimethoxysilane; wherein the mass ratio of the glass fiber to γ-methacryloxypropyltrimethoxysilane is 90:(2-5), and the diameter of the glass fiber is 8-20 μm; The chain extender is at least one of ethylene glycol, propylene glycol, 1,3-butanediol and 2-methyl-1,3-propanediol; The catalyst is at least one of stannous isooctanoate, potassium 2-ethylhexanoate and dibutyltin dilaurate, and the antioxidant is one of antioxidant 1010, antioxidant 1076 and antioxidant 164; The preparation method of the antibacterial agent is as follows: 0.78g of silver nitrate is added to 100mL of deionized water to prepare a 7.8g / L silver nitrate solution; 0.1g of sodium borohydride is added to 100mL of deionized water to prepare a 1g / L sodium borohydride solution; 20mL of the silver nitrate solution is added dropwise to 4% dilute ammonia water, while shaking until the precipitate is just dissolved, to obtain a silver ammonia solution; 20mL of the prepared silver ammonia solution is added to 80mL of an aqueous polyurethane emulsion with a solid content of 32% and stirred evenly to obtain a mixed solution, and 6mL of the sodium borohydride solution is added to the mixed solution, stirred for reaction, to obtain the antibacterial agent; The coupling agent is a composition of 3-aminopropyltriethoxysilane, decyltrimethoxysilane, octyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:(2-4):(3-5):1; The method for preparing the high-performance polyether TPU film comprises the following steps: S101, respectively adding dimer acid polyester polyol, modified polyester polyol, polyisocyanate, nitrile rubber, modified glass fiber, chain extender, catalyst, hexafluorobutyl methacrylate, coupling agent, antioxidant and antibacterial agent into a stirring tank according to their weight proportions, setting the speed to 300 rpm, controlling the temperature at 53° C., stirring for 10-15 min, and obtaining a mixture; S102. The mixed material is transferred into a preheated twin-screw extruder for melt extrusion, and then granulated by a pelletizer, and finally blown into a film by a film blowing machine to obtain a high-performance polyether TPU film with a thickness of 0.01-0.03 mm; the extrusion temperatures of the twin-screw extruder from the feed port to the die are 140°C, 170°C, 180°C, 190°C, 200°C, 210°C, and 200°C respectively; the die head temperature of the film blowing machine is set to 180°C, 185°C, and 180°C.

Citation Information

Patent Citations

  • TPU bonding layer for heat-sealing adhesive tape, three-layer heat-sealing adhesive tape comprising TPU bonding layer as well as preparation method and application of three-layer heat-sealing adhesive tape

    CN109762503A

  • TPU film with high hydrophobic angle, and preparation method thereof

    CN110835463A

Cited By

  • Waterproof and antibacterial soft air cushion powder puff and preparation method thereof

    CN120134772A

  • Waterproof and antibacterial soft air cushion powder puff and preparation method thereof

    CN120134772B